2012
DOI: 10.1155/2012/259571
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacteria in Coral Reef Ecosystems: A Review

Abstract: Cyanobacteria have dominated marine environments and have been reef builders on Earth for more than three million years (myr). Cyanobacteria still play an essential role in modern coral reef ecosystems by forming a major component of epiphytic, epilithic, and endolithic communities as well as of microbial mats. Cyanobacteria are grazed by reef organisms and also provide nitrogen to the coral reef ecosystems through nitrogen fixation. Recently, new unicellular cyanobacteria that express nitrogenase were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(87 citation statements)
references
References 95 publications
2
77
0
1
Order By: Relevance
“…Several studies describe the occurrence of harmful blooms, particularly of thermo-tolerant species (e.g. Hallock 2005;Paul et al 2005;Paul 2008;Smith and Schindler 2009;Charpy et al 2012). Dense cyanobacterial mats can have a variety of negative effects on reef communities: they inhibit recruitment (Kuffner et al 2006), act as pathogens (Carlton and Richardson 1995), overgrow and smother reef benthos (Ritson-Williams et al 2005;De Bakker et al 2016b), create an anoxic environment (Brocke et al 2015b) and produce chemicals that cause coral and fish mortality (Nagle and Paul 1998).…”
Section: Communicated By Ecology Editor Dr Alastair Harbornementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies describe the occurrence of harmful blooms, particularly of thermo-tolerant species (e.g. Hallock 2005;Paul et al 2005;Paul 2008;Smith and Schindler 2009;Charpy et al 2012). Dense cyanobacterial mats can have a variety of negative effects on reef communities: they inhibit recruitment (Kuffner et al 2006), act as pathogens (Carlton and Richardson 1995), overgrow and smother reef benthos (Ritson-Williams et al 2005;De Bakker et al 2016b), create an anoxic environment (Brocke et al 2015b) and produce chemicals that cause coral and fish mortality (Nagle and Paul 1998).…”
Section: Communicated By Ecology Editor Dr Alastair Harbornementioning
confidence: 99%
“…Increased occurrence of reef dwelling cyanobacterial blooms has been found on coral reefs around the world (e.g. Charpy et al 2012). It is plausible that a decline in water quality and elevated water temperature initiated the recent shift to dominance of BCM on these reefs (Brocke et al 2015a;Den Haan 2015).…”
Section: The Rise Of Bcm and Spongesmentioning
confidence: 99%
“…Microbial mats dominated by benthic, filamentous species of cyanobacteria also play a large role in coral diseases leading to reef decline (e.g. Black Band Disease); however, the predominant microbial autotrophs in oligotrophic waters surrounding coral reef ecosystems and lagoons are Synecchococcus and Prochlorococcus spp., genera which are not likely to be pathogens in the marine environment [7].…”
Section: Resultsmentioning
confidence: 99%
“…Similar most abundant taxa were also among the most abundant on the surfaces of crustose coralline algae, CCA (Sneed et al, 2015). Cyanobacteria, which were found in highest numbers at the inshore site (LL), are often an indicator for bad water quality and eutrophic conditions (Agawina et al, 2003;Paerl et al, 2011) and may inhibit coral recruitment (Charpy et al, 2012), while Alphaproteobacteria, which had the lowest abundance at the inshore site, are often associated with more oligotrophic systems (Yin et al, 2013) and were found to be dominant on CCA surfaces, where their decrease was shown to reduce coral larvae settlement (Webster et al, 2011). These findings corroborate the assumption that the environmental conditions at the inshore site, which was most affected by anthropogenic impacts from nearby Makassar, accommodate a certain BCC accustomed to these conditions.…”
Section: Bacterial Communitiesmentioning
confidence: 99%